Design and Development of Multiband Antennas for Wireless Communication (International Journal of Communication Systems and Network Technologies, 2013)
Recent developments in the field of wireless communication industry continue to drive the requirements for small, compatible, and affordable multiband antennas. A new multiband antenna is proposed to face the challenges of multi-frequency operation. In this paper, a microstrip patch antenna with a T-slit or without T-slit is designed for multiband operations. This antenna shows the three distinct frequency bands, centered at 4.02 GHz, 6.18 GHz and 11.13 GHz. Furthermore, to increase the frequency bands the same antenna structure is modified by attaching a T-shaped slit on the radiating patch. This proposed modified antenna has four distinct operating frequency bands centered at 3.92 GHz, 5.82 GHz, 7.88 GHz and 11.35 GHz with improved return loss. The proposed antennas has compact size of 25 X 28 X 0.82 mm3 including the ground plane and both antenna structures are designed on FR-4 substrate (Dielectric constant = 4.4) of thickness h = 0.8 mm. The proposed structures were simulated by using the electromagnetic (EM) simulation software. The simulated return losses are less than -10 dB at resonance frequencies. The presented antennas are suitable for multiband wireless communication systems. The Tetra-band antenna with compact size of 25 X 28 X 0.82 mm3 including the ground plane is fabricated using FR-4 substrate (Dielectric constant = 4.4) of thickness h = 0.8 mm.
Keywords: Multiband; Microstrip Feed Line; Resonance Frequency; Rod-Shaped Parasitic Element; Slit; Slot